2010
DOI: 10.1371/journal.pone.0013531
|View full text |Cite
|
Sign up to set email alerts
|

E-β-Ocimene, a Volatile Brood Pheromone Involved in Social Regulation in the Honey Bee Colony (Apis mellifera)

Abstract: BackgroundIn honey bee colony, the brood is able to manipulate and chemically control the workers in order to sustain their own development. A brood ester pheromone produced primarily by old larvae (4 and 5 days old larvae) was first identified as acting as a contact pheromone with specific effects on nurses in the colony. More recently a new volatile brood pheromone has been identified: E-β-ocimene, which partially inhibits ovary development in workers.Methodology and Principal FindingOur analysis of E-β-ocim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
120
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 124 publications
(128 citation statements)
references
References 44 publications
6
120
1
1
Order By: Relevance
“…Mohammedi et al (1998) showed that among the ten esters, ethyl palmitate and methyl linolenate are the compounds that are involved in the prevention of ovary development of bees. All of the ten esters (boiling point around 200 °C) generally known as brood pheromone are non-volatile and their movement is likely facilitated by worker to worker contact (Pankiw, 2004a;Maisonnasse et al, 2010). Very recently, a new highly volatile molecule, E-β-ocimene, has been identified in larvae (Maisonnasse et al, 2009).…”
Section: Interactions Between Adults and Broodmentioning
confidence: 99%
See 4 more Smart Citations
“…Mohammedi et al (1998) showed that among the ten esters, ethyl palmitate and methyl linolenate are the compounds that are involved in the prevention of ovary development of bees. All of the ten esters (boiling point around 200 °C) generally known as brood pheromone are non-volatile and their movement is likely facilitated by worker to worker contact (Pankiw, 2004a;Maisonnasse et al, 2010). Very recently, a new highly volatile molecule, E-β-ocimene, has been identified in larvae (Maisonnasse et al, 2009).…”
Section: Interactions Between Adults and Broodmentioning
confidence: 99%
“…Very recently, a new highly volatile molecule, E-β-ocimene, has been identified in larvae (Maisonnasse et al, 2009). This brood pheromone component also acts as a primer pheromone with two actions on worker bee physiology: inhibition of worker ovaries (Maisonnasse et al, 2009) and acceleration of worker bee behavioural maturation (Maisonnasse et al, 2010). E-β-ocimene (boiling point 73 °C), which belongs to the terpene family, is volatile so and therefore has an aerial transmission and is easily dispersed within the colony (Maisonnasse et al, 2010).…”
Section: Interactions Between Adults and Broodmentioning
confidence: 99%
See 3 more Smart Citations